Influence of core material and occlusal contact pattern on fatigue behavior of different monolithic ceramic crowns - Packaeser, Maria Gabriela; Machry, Renan Vaz; Grassi, Elisa Donaria Aboucauch [UNESP]; Saavedra, Guilherme de Siqueira Ferreira Anzaloni [UNESP]; Kleverlaan, Cornelis Johannes; Valandro, Luiz Felipe; Tribst, João Paulo Mendes; Pereira, Gabriel Kalil Rocha (Elsevier, 2025)
This study evaluated the effect of substrate core materials and occlusal contact patterns on the fatigue mechanical behavior and stress distribution of single-unit ceramic crowns. One hundred and twenty monolithic crowns were fabricated from zirconia (YZ – IPS e.max ZirCAD, Ivoclar), lithium disilicate (LD – IPS e.max CAD, Ivoclar) and polymer infiltrated ceramic network (PICN – Enamic, Vita Zahnfabrik). The crowns were allocated considering two factors: 'substrate' (epoxy resin or cast Ni-Cr metal core) and 'occlusal contact pattern' (contact at the cusp ridges or cusp tips). The substrate models were design, milled and scanned to plan the restorations in a digital workflow. The crowns were milled, bonded to the substrates, and subjected to an accelerated fatigue test (100 N; 10,000 cycles/step; 20 Hz step-size: 100 N up to 1600 N, and after, 200 N until failure or survival at 2,800N; immersed in water). Statistical analyses were performed using two-way ANOVA, Tukey's post-hoc test, and Kaplan-Meier survival analysis (α = 0.05) considering fatigue failure load and cycles for fatigue failure (FFL/CFF). Fractographic and finite element analysis (FEA) were carried out. The results indicate that the 'substrate' factor did not influence the mechanical behavior of YZ and LD monolithic crowns (p > 0.05). However, PICN crowns bonded to epoxy resin exhibited statistically superior results for FFL and CFF (p < 0.05) compared to Ni-Cr cores. Regarding the 'occlusal contact pattern' factor, YZ and LD exhibited higher mean FFL and CFF when associated with cusp tip contact compared to cusp ridge contact (p < 0.05), except for YZ bonded to the epoxy resin substrate (p > 0.05). No differences were detected for the 'occlusal contact' factor in PICN crowns (p > 0.05). The predominant failure was Hertzian cone cracks, regardless of the restorative material. Stress measurements showed higher stress peaks at the cusp ridges. The core material did not alter the fatigue mechanical behavior of YZ or LD crowns. However, the incidence of cusp ridge contacts in YZ or LD crown increases the risk of failure. Conversely, when using PICN crowns, a core with a more similar elastic modulus enhances mechanical behavior compared to a stiffer core, and no influence on the occlusal pattern was observed.
Keywords: Dental ceramics; Fatigue; Finite element analysis; Mechanical phenomena; Survival